2020
DOI: 10.3390/molecules25020324
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioactivity of Thiosemicarbazones Containing Adamantane Skeletons

Abstract: Reaction of 4-(1-adamantyl)-3-thiosemicarbazide (1) with numerous substituted acetophenones and benzaldehydes yielded the corresponding thiosemicarbazones containing adamantane skeletons. The synthesized compounds were evaluated for their in vitro activities against some Gram-positive and Gram-negative bacteria, and the fungus Candida albicans, and cytotoxicity against four cancer cell lines (Hep3B, HeLa, A549, and MCF-7). All of them showed good antifungal activity against Candida albicans. Compounds 2c, 2d, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In recent years, thiosemicarbazones have mostly been exploited for their antimicrobial and anticancer activities in the development of new drugs. Various studies have reported the antifungal activity of a series of thiosemicarbazone derivatives against Candida species [ 21 , 22 , 23 ]. Additionally, compounds bearing ligand recognition ability have been screened against Candida species.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, thiosemicarbazones have mostly been exploited for their antimicrobial and anticancer activities in the development of new drugs. Various studies have reported the antifungal activity of a series of thiosemicarbazone derivatives against Candida species [ 21 , 22 , 23 ]. Additionally, compounds bearing ligand recognition ability have been screened against Candida species.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33]. In addition, thiosemicarbazones (TSCs) have a wide clinical antitumor spectrum with efficacy in various tumor types such as bladder cancer, pancreatic cancer, cervical cancer, non-small cell lung cancer, breast cancer, prostate cancer and leukemia [34][35][36][37]. Figure 3 shows some representative compounds with thiosemicarbazones structure in the clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…1) reduces the reproducibility of vaccinia virus, and also exhibits activity in vitro against some Gram-positive and Gramnegative bacteria and fungi. 2,3 Substituted aminoacetyladamantylamines B exhibit inhibitory activity against vaccinia virus (Fig. 1).…”
mentioning
confidence: 99%
“…1). 3 1-Adamantanecarboxylic acid amide containing the (-)-10-amino-2-pinene fragment (structure C) 4 and N-(1-adamantyl)-2,2-diphenylacetamide D proved to be effective inhibitors of smallpox virus. 5 In addition, compounds containing the adamantyl fragment such as memantine E (Fig.…”
mentioning
confidence: 99%